Stormbreaker : the graphic novel - Johnston, Antony; Damerum, Kanako; Takasaki, Yuzuru; Horowitz, Anthony, 1955- (New York : Philomel, 2006)
Soon to be a major motion picture, this very first Alex Rider adventure, featuring manga-like illustrations, follows a fourteen-year-old boy, who, after the death of the uncle who had been his guardian, is coerced into continuing his uncle's dangerous work for Britain's intelligence agency, MI6
"The #1 New York Times best-selling series Alex Rider"--Cover
"Based on the original novel Stormbreaker"--Colophon
Keywords: Horowitz, Anthony, -- 1955- -- Adaptations; Rider, Alex (Fictitious character) -- Comic books, strips, etc; Spies -- Comic books, strips, etc; Terrorism -- Comic books, strips, etc; Orphans -- Comic books, strips, etc; England -- Comic books, strips, etc; Children's stories; Graphic novels; Spy fiction; Adaptations; Comic books, strips, etc; Fiction; Graphic novels; Juvenile works; Spy stories; Print books